DEVELOPMENT OF RUNWAY PAVEMENT STRUCTURE MAINTENANCE PROGRAM WITH LIFE CYCLE COST ANALYSIS METHOD: A CASE STUDY OF SOEKARNO HATTA INTERNATIONAL AIRPORT - Natali Putriana, Stephanie
Runway pavement structures serve several functions, including providing bearing capacity to the subgrade, facilitating a smooth ride for aircraft, and creating friction between aircraft landing gear and the pavement surface. Over time, aircraft loading results in a reduction in the structural and functional performance of pavement structures. In order to maintain the structural and functional performance of the runway pavement as the volume of flight traffic grows, it is necessary to implement a maintenance program which is capable of guaranteeing that performance meets or exceeds the required minimum service standards. The limited budget available to the airport authority requires the maintenance program to be structured in a way that ensures the structural and functional performance of the pavement structure meets the minimum service standards while also taking into account the financial constraints. The formulation of the runway maintenance program at Soekarno-Hatta International Airport was conducted using the life cycle cost analysis method, with the maintenance costs of four scenarios being compared with Runway 06-24 as the object of research. The process of scenario development involved an evaluation of existing structural performance, existing functional performance, and the projection of patterns of structural and functional performance deterioration over a 20-year analysis period (2024-2044). The structural performance indicator used in this analysis is the Pavement Condition Number (PCN) and the functional performance indicators are roughness, skid resistance, and pavement condition index (PCI). The evaluation results indicate that the existing structural performance of the runway 06-24 pavement structure is insufficient to accommodate the projected annual average aircraft movement of 149,226 departures over the 20-year plan period. The evaluation results from the functional performance indicators indicate that the roughness, skid resistance, and pavement conditions index remain above the minimum service standard. The pattern of structural performance decline indicates that the current age of the runway 06-24 pavement structure will reach the end of its operational life in 2035. In accordance with the deterioration curve, which indicates a decline in functional performance, the PCI value is projected to decline by 0,65 points per year for section 1 (STA 0+000 - STA 0+860) and section 3 (STA 2+370 – 3+000). Section 2 (STA 0+860 - STA 2+370) is predicted to decrease by 0.44 points/year if a functional maintenance is not implemented. The development of maintenance program scenarios was performed by taking into account historical maintenance activities, existing performance evaluations, and future performance predictions during the analysis period. The first maintenance program scenario involved a structural overlay in 2025, while the second scenario involved a scrape and fill method in 2025. The third scenario consisted of a combination of patching and crack sealing, with periodic implementation every five years, followed by a structural overlay in 2035, which aligned with the projected end of the pavement's remaining life. The fourth scenario consisted a functional overlay with a periodic implementation every five years, followed by a structural overlay in 2035, which aligned with the projected end of the pavement's remaining life. The recommended pavement structure maintenance programme, based on a life cycle cost analysis, is the first maintenance scenario, which involves structural-based maintenance in the form of overlay with HMA material (P-401/403) with a design thickness of 7.5 cm. The first scenario is scheduled to be implemented in 2025. The total cost of maintenance throughout the entire life cycle was Rp 36,539,000,000 (thirty-six billion, five hundred and thirty-nine million rupiah). The final PCI values for the first maintenance scenario at the of analysis period are 87,7 in section 1 and section 3; 91.6 in section 2; and a final PCN value of 64. The implementation of structural-based maintenance not only enhances the structural performance of the pavement structure but also restores its functional performance to the condition that initially existed at the time of the runway's construction. The delay of structural performance maintenance can result in the requirement for greater maintenance costs in the future. The deterioration of structural performance that is neglected can lead to a reduction in functional performance, as indicated by damage on the surface, such as rutting and cracks, which are typical forms of damage observed on Runway 06-24.